Rainforest World Music Festival - Sarawak Tourism Board (Malaysia : Virtual Malaysia. Com, 2007)
The festival features a wide range of performances from traditional music, to world fusion and contemporary world music. The festival emphasizes the use of traditional acoustic world instruments, although electric accompaniment instruments are common. Invited performers are prominent artists from Sarawak, other provinces of Malaysia, surrounding countries, and from around the world
VCD format
Keywords: Music festivals -- Sarawak; Musical instruments